Form in Coleridge, and in Perception and Art More Generally - Reid, Nicholas (Romanticism on the Net)

(untitled) (Université de Montréal, 2002)
Abstract We should not think of aesthetic form in terms of shape, but rather, as Susanne Langer argues, as a reflection of "orderliness" or relation. When thinking of form, we should not think of Keats's Grecian urn (embodying in its shape the beauty of the eternal)--not, at least, if this leads us to think of the urn's reified shape as somehow fundamental and therefore a kind of language. Rather, we should think of the relation between binary code and the image it produces on a computer screen, as prototypically "formal." Such images certainly do have shape, but those shapes are the product of underlying acts (here a set of computer instructions), which accordingly are more fundamental. This allows us to understand Coleridge's mature insistence on the reciprocal formality of the Father and the Son (for in any case the Son cannot have "shape" in any spatial sense). It also allows us to rehabilitate Coleridge's problematic concept of organic form. Building on Louis Arnaud Reid's arguments against the representative theory of perception, I argue that the qualitative dimensions of everyday sensory perceptions cannot in themselves be characterized by primary qualities like spatial shape, for it is absurd to think that we have anything like Polaroid snapshots floating around within our synapses. Rather, the qualitative dimensions of sensory perception (colour, perceived shape, and so forth) are "presentations" of the relevant aspects of the world--presentations which bear a formal relation rather than immediate likeness to the world. Sense-perception is thus "formal." And we can thus also claim that an art work formally embodies its meanings; that the concept of "form" has work to do; and that form is implicitly qualitative, being characterized by texture, sound qualities, shapeliness, etc..